ISOLASI DAN KARAKTERISASI PULP TANDAN KOSONG KELAPA SAWIT - Dini, Dini Pratiwi; Lubis, Rosliana (Jurnal Agro Fabrica, 2024)
This study aims to isolate and characterize pulp derived from oil palm empty fruit bunch fibers. Oil palm empty fruit bunch fiber has great potential as an alternative raw material in the paper industry due to its abundant availability and environmentally friendly nature. The pulp isolation process was carried out using acid and base hydrolysis methods. Characterization carried out includes measurement of cellulose content and pulp quality analysis. Pulp quality parameters analyzed included initial milled degree, bright degree, number of stains, extractive content (dichloromethane), moisture content (AD), and mechanical strength indices, such as tear index, crack index, and tensile index at a milled degree of 300 ml CSF. The results showed that the pulp produced from oil palm empty fruit bunch fibers through the acid-base hydrolysis process had a cellulose content of 56-58%. The quality analysis of this pulp refers to the quality requirements according to SNI 6107 for leaf-bleached Kraft Pulp (LBKP).